2023
DOI: 10.3389/fpubh.2023.1179755
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression, and insomnia among nurses during the full liberalization of COVID-19: a multicenter cross-sectional analysis of the high-income region in China

Abstract: IntroductionFrontline nurses fighting against the epidemic were under great psychological stress. However, there is a lack of studies assessing the prevalence rates of anxiety, depression, and insomnia among frontline nurses after the full liberalization of COVID-19 in China. This study demonstrates the impact of the full liberalization of COVID-19 on the psychological issues and the prevalence rate and associated factors of depressive symptoms, anxiety, and insomnia among frontline nurses.MethodsA total of 17… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Little evidence on how COVID-19 optimization policies influence depression symptoms among those infected in China. We found that the prevalence of depression symptoms was 35.3% which was similar to the study conducted in Pokhara ( 38 ) and China ( 25 ). The potential for temporary unemployment, reduced salary, and strained medical resources during the early stages of implementing the COVID-19 optimization policy may exacerbate psychological distress among the public.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Little evidence on how COVID-19 optimization policies influence depression symptoms among those infected in China. We found that the prevalence of depression symptoms was 35.3% which was similar to the study conducted in Pokhara ( 38 ) and China ( 25 ). The potential for temporary unemployment, reduced salary, and strained medical resources during the early stages of implementing the COVID-19 optimization policy may exacerbate psychological distress among the public.…”
Section: Discussionsupporting
confidence: 88%
“…These measures notably reduced mobility restrictions on the population and adjusted the isolation methods for infected individuals, particularly those with asymptomatic or mild cases. Studies have shown that 80% to 90% of the public in China was infected with SARS-CoV-2 between December 2022 to January 2023 ( 24 , 25 ). Certain factors may contribute to an increased risk of depression symptoms among individuals infected with SARS-CoV-2 after optimizing the COVID-19 response in China.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that contemporary nurses are more susceptible to mental health issues, such as anxiety, depression, job burnout, sleep disturbances, and poor psychological resilience [1][2][3]. Among them, anxiety and depression are the most common psychological problems [4,5]. Moreover, The COVID-19 pandemic has resulted in a rapid increase in nursing workload that further exacerbates these psychological challenges [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study from the COVID-19 era in over 4,000 hospital nurses in China reported rates of 18 and 12% for moderate to severe depressive symptoms and insomnia, respectively (Liang et al, 2021). A recent survey of nearly 1,800 frontline hospital nurses during full liberalization of COVID-19 showed alarmingly high rates of both depressive symptoms (69%) and insomnia (77%, Xiao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%